The ascent of man : a philosophy of human nature - Harris, James F. (James Franklin), 1941- (Transaction, 2011)
"The Ascent of Man develops a comprehensive theory of human nature. Harris sees human nature as an emergent property that supervenes upon the causal nexus that is created by the interactions amongst a cluster of properties. While there is significant overlap between individuals that have human nature and those that are biologically human, the concept of human nature developed in this book is different from what it means to be biologically human. Whether biologically human or not, an individual may be said to possess human nature. This theory of human nature is called the "cluster theory."